Silk Fibroin-Based Materials for Catalyst Immobilization - Shanshan Lv (Molecules, 2020)
Silk fibroin is a widely and commercially available natural protein derived from silkworm cocoons. Thanks to its unique amino acid composition and structure, which lead to localized nanoscale pockets with limited but sufficient hydration for protein interaction and stabilization, silk fibroin has been studied in the field of enzyme immobilization. Results of these studies have demonstrated that silk fibroin offers an important platform for covalent and noncovalent immobilization of enzymes through serving as a stabilization matrix/support with high retention of the biological activity of the enzymes of interest. In the hope of providing suggestions for potential future research directions, this review has been written to briefly introduce and summarize key advances in silk fibroin-based materials for immobilization of both enzymes/biocatalysts (including alkaline phosphatase, β-glucosidase, glucose oxidase, lipase, urease, uricase, horseradish peroxidase, catalase, xanthine oxidase, tyrosinase, acetylcholinesterase, neutral protease, α-chymotrypsin, amylase, organophosphorus hydrolase, β-galactosidase, carbonic anhydrase, laccase, zymolyase, phenylalanine ammonia-lyase, thymidine kinase, and several others) and non-enzymatic catalysts (such as Au, Pd, Fe, α-Fe2O3, Fe3O4, TiO2, Pt, ZnO, CuO, Cu2O, Mn3O4, and MnO2).